Positioning design profession in a belief system: an approach to integrate tawhidic principles in design learning and practice - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (2013)
Tawhidic principles are concepts of al-iman (belief), al-ilm (knowledge) and al-amal (pious acts and efforts). Al-iman is the belief in the existence of one God and creator, with a commitment to his teachings and revelations. Therefore, design which is believed to be value based requires a holistic approach as this will help in observing the built and natural environment using critical eyes and mind; and also build highly effective habits in designers as a local player to address local issues and as a global player for the betterment of the world. In the light of this, this paper seeks the knowledge regarding belief system, gives the general overview of tawhidic principles, illuminates on design learning and finally tried to integrate tawhidic principles in design learning and practice by proposing five approaches that can be used in design practice.